MicroRNAs in multiple myeloma and related bone disease - Rossi, Marco (Ann Transl Med, 2015)
MicroRNAs (miRNAs) are short non coding RNAs aberrantly expressed in solid and hematopoietic malignancies where they play a pivotal function as post-transcriptional regulators of gene expression. Recent reports have unveiled a central role of miRNAs in multiple myeloma onset and progression and preclinical findings are progressively disclosing their potential therapeutic value as drugs or targets. In this review, we provide the basic insights of miRNA biology and function, showing how these molecules are extensively dysregulated in malignant plasma cells (PC) and related microenvironment, thus favoring clone survival and proliferation. We here describe how these critical activities have recently been evaluated to design miRNA-based therapies against multiple myeloma cells and its surrounding microenvironment.